Способ базирования заготовки при дорновании - Скворцов В. Ф. Владимир Федорович; Арляпов А. Ю. Алексей Юрьевич; Данилов Н. В.; Каменев С. А.; Печенкин С. Г.; Охотин И. С. Иван Сергеевич
опубл. 27.05.05